Development of algorithms for effective control of process of testing induction motors by mutual load - V. V. Kharlamov; D. I. Popov (Омский научный вестник, 2019)
The urgency of the development of energy-efficient electrical systems designed for testing induction machines is formulated. The necessity of automation of test stands in order to increase their reliability is noted. As research object selected scheme for testing of induction motors by mutual loads. For these schemes, efficient control algorithms have been developed, eliminating the possible overload during the starting and subsequent loading of electric machines to the nominal mode. The results obtained in the study can be applied in the production and operation of induction machines.